Peran Good Corporate Governance dalam Memoderasi Pengaruh Profitabilitas, Leverage, dan Corporate Social Responsibility (CSR) terhadap Nilai Perusahaan - Qonita Aufa Dina; Mentari Dwi Aristi; Siti Rodiah (Akuntansi & Ekonomika, 2020)
This research aims to find out the role of good corporate governance in moderating the effects of profitability, leverage, and corporate social responsibility on firm value. The population in this study amounted to 58 companies. Sample selection setting by purposive sampling method and the specific criteria are as many as 9 companies with 45 total observations. Analytical technigues used multiple linear regression analysis for hypothesis 1-3, and multiple linear regression analysis with Moderated Regression Analysis (MRA) test for hypothesis 4-6 by using SPSS 20. The results show that profitability has a positive effect on firm value, meanwhile leverage and corporate social responsibility has no effect on firm value. Good corporate governance does not strengthen or weaken the effect of profitability, leverage, and corporate social responsibility on firm value partially.